PENGARUH BIAYA AGENSI, STRUKTUR KEPEMILIKAN, DIPERSION OF OWNERSHIP, DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DEVIDEN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2007-2011 - Fasridon Fasridon (Pusat Riset dan Inovasi Nasional, 2022)
The capital market is an investment vehicle for those who have excess funds. People invest in the capital market with the aim of earning income or return on investment. Investment can be defined as an activity of placing funds in one or more assets during a certain period in the hope of obtaining income and or increasing the value of the investment. The main purpose of the company to invest is the rate of return. The main purpose of investors investing their funds in securities is, among others, to get the maximum rate of return through policies, for example, dividends at a certain risk will get certain results with minimal risk. From the results of the research, it is found that there is a negative influence of Ownership Structure, a positive influence of Dispersion of Ownership, and a negative influence of Capital Structure on the Dividend Policy of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2007-2011.